The Effect of Independence, Competence, and Audit Complexity on Internal Audit Quality - Jamarang, Satriani; Pontoh, Grace T.; Maghfirah, Rahmi Nur; Wadi, Syamsuddin (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
The goal of this study was to see how independence affected internal audit quality, how competence affected internal audit quality, and how audit complexity affected internal audit quality. The population of this study is all internal auditors, particularly those working at PT PLN (Persero) SPI Audit Region X, and the sample size is 40 respondents. This research technique, The sample in this research are primary data in the questionnaire form that included respondents' analyses of the audit's independence, competence, and complexity on the quality of internal audit. According to the findings of this study, independence has a significant impact Competence has a significant effect on the quality of internal audit, while audit complexity has no effect on the quality of internal audit. This study is expected to aid in the production of high-quality internal audit reports by improving and changing attitudes, as well as improving auditor performance in a positive direction in order to produce good financial results